Analisis Efisiensi Teknis dan Faktor Penentunya pada Usahatani Kentang (Solanumtuberosum L.) di Kota Pagar Alam, Provinsi Sumatera Selatan - Maryanto, M. Agus; Sukiyono, Ketut; Priyono, Basuki Sigit (Program Studi Agribisnis, Fakultas Pertanian, Universitas Muhammadiyah Yogyakarta, 2018)
This study aims to determine and analyseÂ the level of technical efficiency and the factors influencing technical efficiency of aÂ potato farming in North Dempo, sub-district Pagar Alam City, South Sumatera Province using 51 farmers who are censused.Â Frontier production function, estimated using the MLE method, is used to determineÂ the level of technical efficiency. Meanwhile,Â multiple regression estimated using OLSÂ approach is used to determine factors influencing technical efficiency level. The research showed that, land area, seed, organicÂ fertilizer, ZA fertilizer, Ponska fertilizer, andÂ fungiside were significantly affect potatoÂ production. The research finds that the levelÂ of technical efficiency of potato farmingÂ was, on the average, 81.336 percent. TheÂ research also shows that the intensity of extension and farmersâ experience affect significantly and negatively technical inefficiency while formal education, age, and land ownership status do not.